External Linkages and Contagion Risk in Irish Banks - Mitra, Srobona (IMF Working Papers; Working Paper, 2007)
The large and growing international linkages of big Irish banks expose them to idiosyncratic shocks arising in other countries. We analyze international interdependencies of Irish banks-during both normal times and in periods of large shocks or extreme events-using an existing methodology with distance to default (DD) data constructed from the banks' equity prices. The data covers daily observations from January 1994 to November 2005. We first construct rolling correlations between DDs of Irish banks and those of banks from other European countries and the U.S. to analyze trends in cross-country interdependencies. We then use a multinomial logit model to estimate the number of banks in Ireland that experience a large shock on the same day as banks in other countries ("coexceedances"), controlling for Ireland-specific and global factors. We find evidence of increasing cross-border interdependencies over time; differing interlinkage patterns in the pre-Euro, post-Euro, and the post-September 11th periods; and significant cross-border contagion risk from the United Kingdom, the United States, and the Netherlands. This Working Paper should not be reported as representing the views of the IMF. The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate.